Influence of Micro, Small & Medium Enterprises Taxpayer Compliance Factors in Bandung - Callista Grace Hagny; Dian Sadeli (Masyarakat Ekonomi Syariah Bogor, 2024)
The Indonesian State Revenue and Expenditure Budget (APBN) is primarily funded by taxes. There are 65.5 million micro, small, and medium-sized enterprises (MSMEs) in Indonesia, making them a sector with a significant potential to assist with tax payments. In order for MSMEs to actively participate in taxation, the government continues to provide various facilities. The Indonesian tax self-assessment system, on the other hand, grants the taxpayer authority to determine the amount of tax owed, which necessitates the taxpayer's awareness and complete compliance. As a result, research was conducted on the factors that influence MSME taxpayer compliance, using tax knowledge, taxpayer awareness, and taxpayer motivation as the variables. Using a purposive sampling strategy, this study selected 100 MSMEs from Bandung with diverse industrial backgrounds and characteristics as the sample population. This study employs quantitative and explanatory analysis methods, as well as a questionnaire as the research medium. PLS-SEM was also used for analysis, and two assessments, the measurement model (validity) and the structural model assessment, were performed. This study found that taxpayer awareness has no significant impact on tax compliance, while tax literacy and taxpayer motivation have a significant impact. Accurate tax reporting and payment are supported by solid literacy. Because taxpayers are unaware of government losses, their awareness has less of an impact. Compliance is largely driven by internal and external motivation